From the Closet of the Mind to Mindedness: Rethinking 'Animism' at the Crossover of Science Studies, Postcolonial Ethnography and Environmental Humanities - Fani Cettl (Janeway JS, 2018)
Recently the concept of animism has been radically rethought at the crossover of postcolonial ethnography, environmental humanities and science studies. This reconceptualization aims at decolonising western sciences, destabilising an anthropocentric world picture, and articulating an environmental and animal ethics in the age of the Anthropocene. It decidedly abandons the controversial colonial epistemology in which animism was first introduced as a primitive and regressive belief in the supernatural spirits. In this essay I would like to situate this current rethinking of animism into a genealogy of historical discourses, following scholarship that has theorized one aspect of the Enlightenment secularisation processes as the internalisation of spirits and ghosts from nonhuman materiality on the outside into the space of the human mind. Building on this approach, I propose that the current, post-Enlightenment, posthumanist, cross-disciplinary rethinking of animism can be said to mark a certain historical reversal: an externalization of what has been seen as within and of the human mind, which I will in this essay term mindedness, to the outside nonhuman materiality (again).